2013
DOI: 10.1056/nejmoa1113849
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Daily Chlorhexidine Bathing on Hospital-Acquired Infection

Abstract: BACKGROUND Results of previous single center observational studies suggest that daily bathing of patients with chlorhexidine may prevent hospital-acquired bloodstream infections (HABSIs) and acquisition of multidrug-resistant organisms (MDROs). METHODS We conducted a multicenter, cluster randomized, non-blinded crossover trial to evaluate the effect of daily bathing with chlorhexidine impregnated washcloths on the acquisition of MDROs and incidence of HABSIs. Nine intensive care and bone marrow transplant un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
373
8
40

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(440 citation statements)
references
References 33 publications
(28 reference statements)
12
373
8
40
Order By: Relevance
“…As stated by the authors, the finding of higher rates of SSIs during warmer months had been previously reported, [2][3][4][5] and the current work further corroborates such observation. As a result, the most important question is perhaps no longer whether seasonal variation in SSIs can occur, but rather, what is the basis for this observation?…”
Section: Seasonal Variation Of Surgical Site Infections: Why Does Itsupporting
confidence: 92%
“…As stated by the authors, the finding of higher rates of SSIs during warmer months had been previously reported, [2][3][4][5] and the current work further corroborates such observation. As a result, the most important question is perhaps no longer whether seasonal variation in SSIs can occur, but rather, what is the basis for this observation?…”
Section: Seasonal Variation Of Surgical Site Infections: Why Does Itsupporting
confidence: 92%
“…129,130 A multicenter, clusterrandomized, non-blinded crossover trial that included patients in HCT units found that daily bathing with chlorhexidineimpregnated washcloths significantly reduced acquisition of MDR organisms and development of hospital-acquired CLABSIs, particularly those caused by gram positive bacteria and fungi. 131 Current clinical trials are evaluating whether receipt of daily chlorohexidine topical skin wipes for 90 days decreases CLABSI rates in children after allo-HCT.…”
Section: Bloodstream Infection Preventionmentioning
confidence: 99%
“…Milstone et al [5] demonstrated a 36% decrease in the incidence of bacteremia in children given daily CHG bathing, with most of the decrease seen in patients with catheterassociated infections (32%). Climo et al [6] in a multicenter, randomized controlled trial of bathing with CHG in adults, found a reduction of 28% in the risk of hospitalacquired infection, as well as a 31% lower rate of primary BSI and a 90% reduction in catheter-associated infections, in comparison with the rates of these conditions in a control group (0.89 with CHG bathing vs. 1.76 in the control group, p = 0.05). In BSI, there was a significant reduction in numbers of gram-positive organisms with CHG bathing (46% in children and 56% in adults), and such bathing also significantly reduced colonization with vancomycin-resistant enterococci (VRE) and MRSA in adults.…”
Section: Chlorhexidinementioning
confidence: 96%